1990
DOI: 10.1093/oxfordjournals.humrep.a137178
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of 1-cell mouse embryos on different cell supports

Abstract: The development of 1-cell mouse embryos in explanted oviducts, on mouse and bovine oviduct epithelial cells and on two established cell line supports is compared. The best rates of blastocyst formation were obtained using explanted oviducts; mouse and to a lesser extent, bovine oviduct epithelial cells allow good embryonic development, associated with high viability after transfer of the blastocysts obtained in co-culture. MDBK (from bovine kidney) and Vero (from Green monkey kidney) have been tested. MDBK all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

1991
1991
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 0 publications
2
41
2
Order By: Relevance
“…In contrast, control 2-cell embryos cultured in T6VA in parallel developed to blastocysts at a high rate (46/60, 76.7%). These experiments confirmed previous results in which coculture of 2-cell mouse embryos on Vero cells using B2 led to poor blastocyst development (8%) (Ouhibi et al, 1990).…”
Section: Menezo's B2supporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, control 2-cell embryos cultured in T6VA in parallel developed to blastocysts at a high rate (46/60, 76.7%). These experiments confirmed previous results in which coculture of 2-cell mouse embryos on Vero cells using B2 led to poor blastocyst development (8%) (Ouhibi et al, 1990).…”
Section: Menezo's B2supporting
confidence: 91%
“…In 1987, Gandolfi and Moor successfully used coculture with sheep oviduct epithelial cells to improve the culture and viability of sheep embryos. Similar studies were subsequently conducted by Eyestone and First (1989) in cattle, Ouhibi et al (1990) and Sakkas and Trounson (1990) in mice and Sakkas et al (1989b) in goats. In the human, coculture using Fallopian tube cells (Bongso et al, 1989;Yeung et a/., 1992) and bovine uterine fibroblast cells (Wiemer et al, 1989) has been reported to improve pregnancy rates; however, the use of controlled epithelial cell lines is more ethically acceptable due to the possibility of introducing viruses and infecting the patient's embryo.…”
supporting
confidence: 59%
See 3 more Smart Citations